Factores asociados a competencias parentales que limitan la autonomía de los niños de nivel primario del CEBE Pacasmayo - provincia de Pacasmayo, 2018. - Correa Gonzáles, Teresa Norhelia (2019)
The purpose of this research was to identify the factors associated with parental competencies that limit the autonomy of children of the primary level with different abilities from the CEBE of Pacasmayo, in the province of Pacasmayo - 2018 To carry out the study, the sample population of 20 families of children attending the Primary Education Center of Primary Level, whose ages range between 04 and 23 years, was taken. The research is descriptive, the instrument used is a questionnaire modified by the thesis for research purposes, the main results show that there is affectivity, family protection and the economic factor that influence parental skills. In conclusion, parental competences are important for the development process of children inside and outside the institution; being these: the affectivity, the family protection and the economic factor. In the introduction; the problematic reality is raised using theories, approaches, and other studies of different authors interested in the same problem to understand the information requested. In material and method, the methodology used for the description of the statistical sampling is presented based on the application of the instrument and the sample obtained from the investigation, resulting in the quantitative and qualitative data of the reality of the investigation. In the presentation and discussion of results, the critical analysis of the information provided by the statistical sampling to describe the final results was expressed, 40% of parents still do not accept their child's disability, the most common diagnoses of children and / or CEBE adolescents with 25% are ASD and Down syndrome and the relevant factor of parental parental competencies, lies in affectivity.